Increasing Women's Resilience to Disasters: An Analysis of Gender Mainstreaming in Natural Disaster Management in Bantul, Indonesia - Ramailis, Nurfadni -; Sakir, Sakir (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2023)
This article looks at how to enhance women's resilience to natural disasters in Bantul, as women are frequently classified as vulnerable groups. It employs qualitative methodologies, utilizing a case study methodology. Data were generally collected through interviews with disaster management authorities and planning sources. Other data were gathered secondarily through library examination, which includes papers, mass media, and other related documents. The findings indicate that the Regional Disaster Management Agency of Bantul has taken positive strides in incorporating gender factors into disaster management strategy. This includes measures to promote women's participation in planning processes, identify special hazards for women, and strengthen women's disaster preparedness. With this discovery, BPBD of Bantul district supports women in the face of disasters by strengthening their capacity through disaster management training and education, as well as disaster planning, in the hope that women's groups can increase women's roles in protecting themselves. This study adds to our understanding of gender marginalization in disaster management and can be used by the government to build more effective policies and programs that involve women in long-term disaster response efforts and promote gender equality.